2017
DOI: 10.1115/1.4035290
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling Performance of Tripod Antivortex Injection Holes Over the Pressure and Suction Surfaces of a Nozzle Guide Vane

Abstract: Film cooling performance of the antivortex (AV) hole has been well documented for a flat plate. The goal of this study is to evaluate the same over an airfoil at three different locations: leading edge suction and pressure surface and midchord suction surface. The airfoil is a scaled up first stage vane from GE E3 engine and is mounted on a low-speed linear cascade wind tunnel. Steady-state infrared (IR) technique was employed to measure the adiabatic film cooling effectiveness. The study has been divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This study, along with the previous investigations [12][13][14][15], showed the influence of side hole locations on tripod hole film cooling. Pressure-sensitive paint was used to measure the film cooling effectiveness for nine branched hole geometries at four blowing ratios of 0.5, 1, 1.5, and 2.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This study, along with the previous investigations [12][13][14][15], showed the influence of side hole locations on tripod hole film cooling. Pressure-sensitive paint was used to measure the film cooling effectiveness for nine branched hole geometries at four blowing ratios of 0.5, 1, 1.5, and 2.…”
Section: Discussionsupporting
confidence: 74%
“…This performance is not observed for any other film cooing hole geometries, including the baseline shaped-hole geometry. The case of θ = 22:5 °with the largest distance between the primary and side holes is the typical tripod shape that is studied by other investigators [12][13][14][15]. In this geometry, the three cylindrical holes flow separately, and the cooling flows do not have many interactions.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…They may, however, compromise the airfoil structural integrity and aerodynamic efficiency. Some studies on discrete film holes include traditional cylindrical holes [3], laidback fanshaped holes [4][5][6][7][8][9], tripod holes [10][11][12][13][14], holes with sister holes [10][11][12][13][14][15][16][17][18], curved diffusion holes [19], and diffusion holes with different exit area geometries [20]. In this paper, we will study a new trench geometry, both experimentally and numerically, and discuss and compare the results.…”
Section: Introductionmentioning
confidence: 99%